Digitalization: Implications for monetary policy - Vivian Chu; Tatjana Dahlhaus; Christopher Hajzler; Pierre-Yves Yanni (Bank of Canada, 2023)
We explore the implications of digitalization for monetary policy, both in terms of how monetary policy affects the economy and in terms of data analysis and communication with the public.
Keywords: C; C4; C8; E; E3; E31; E32; E5; E52; 330; Digitalization; Inflation and prices; Market structure and pricing; Monetary policy; Monetary policy communications; Monetary policy transmission